Pengaruh Pemberian Pupuk Kompos kiambang dan kotoran Ayam Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Muhamad Teja Perdana; Untung Santoso; Antar Sofyan (Universitas Lambung Mangkurat, 2022)
Pakcoy (Brassica rapa .L) is one of the vegetable crop commodities that contains a lot of nutrients and promising economic value. Pakcoy cultivation with an organic farming system using environmentally friendly kiambang and chicken manure can have a positive impact on living things and the environment, making kiambang compost and simple chicken manure can be chopped or can use a chopper. This study aims to determine the effect of kiambang compost fertilizer and chicken manure on the growth and yield of pakcoy (Brassica rapa L.), to determine the dose that has the most effect on the growth and yield of pakcoy (Brassica rapa L.). This research was conducted at the Experimental Field of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, for two months, from January to February 2020. This study used a single factor Randomized Design (RAK) consisting of four compost treatments and one control treatment. The treatments given were kiambang fertilizer and chicken manure (K) which consisted of 5 treatments and 1 control. K0 (0 g polybag-1), K1 = (38.7 g polybag-1) K2 (58.1 g polybag-1), K3 (77.5 g polybag-1), K4 (96.9 g polybag- 1). The observed factor was the dose with four treatments and one control so that 5 treatments were obtained. Each treatment was repeated 5 times so that there were 25 experimental units with a composition of several dose levels. Each experimental unit consisted of 1 plant so that a total of 25 plants in the polybag. Provision of kiambang compost and chicken manure had a significant effect on the growth and yield of pakcoy plants. The best dose of kiambang compost and chicken manure was 40 t ha-1.Copyright ã 2021 Agroekotek View. All rights reserved.Keywords: Dayak onions, tillage, chicken manure